Indonesian Undergraduate Students’ Perception of Their Computational Thinking Ability - Debby Erce Sondakh, S.Kom, M.T, Ph.D; Stenly Richard Pungus; Edson Yahuda Putra (CogITo Smart Journal, 2022)
Become skilled at CT is indispensable for undergraduate students, as the proficiency in information technologies and complex problem solving increase in important in digital workplaces. This study measured Indonesian undergraduate students' self-perception of their CT ability in order to establish CT profile based on gender, majors of specialization, and university location. Study participant comprises of 527 final-year undergraduate students from three universities in Indonesia, using the Hi-ACT instrument. To examine whether statistically significant differences existed, independent sample t-test was used. The findings regarding the profile of Indonesian undergraduates’ CT skill show, the students attained a moderately high CT level. In particular, statistically significant differences existed in Problem Solving and Communication between male and female students, wherein male students means were higher. Regarding majors of specialization, significant differences between STEM and non-STEM students were found in Algorithmic Thinking, Decomposition, Evaluation, Generalization, and Communication, in favor of STEM students. As for university location, significant differences were found in Algorithmic Thinking, Debugging, Teamwork, and Communication, in which suburban students performed better.